PENGARUH INDEKS PEMBANGUNAN MANUSIA, TINGKAT KEMISKINAN, DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Annisa Fadilla Adha; Elfindri Elfindri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2026)
This study examines the influence of the Human Development Index (HDI), poverty rate, and unemployment rate on economic growth across Indonesian provinces during the period 2020–2023. Using secondary data from the Central Bureau of Statistics (BPS), the analysis employs a Fixed Effect Model (FEM) with cluster-robust standard errors to address heteroskedasticity and autocorrelation in panel data. The findings reveal that HDI has a positive and significant effect on economic growth, indicating that improvements in education, health, and overall human capabilities play a key role in stimulating regional economic performance. Meanwhile, the poverty rate shows no significant impact on economic growth, suggesting that short-term economic fluctuations are not immediately sensitive to poverty levels. In contrast, the unemployment rate exhibits a negative and significant effect, demonstrating that higher unemployment reduces productive capacity and dampens economic activity at the provincial level. Overall, the study highlights the critical importance of enhancing human development and strengthening labor market conditions to promote sustainable and inclusive economic growth in Indonesia.